O impacto da implantação da Educação Corporativa à Distância (ECAD) na Companhia Paranaense de Energia - Silva, Nivaldo Pereira da (2010)
The main objective of this work is to evaluate the impact of the long-distance Corporative Education establishment (ECaD), in the developer’s performance of the Companhia Paranaense de Energia - COPEL, the research performed at the Superintendência Regional de Ponta Grossa - Paraná. The actual research has the purpose to analyze the Corporative Education as a way of organizational learning and co-operators developments, in a direct relation among the courses by longdistance Education and the 5 Kirkpatrick levels method. Therefore, the value of the courses evaluations it’s straightly connected to the organizational evaluations results, that is, the investment return on the Corporative Education (RIEC). The company invests in ECaD courses to the developer; and the course involves learning and behavior changes; these changes become into positive attitudes within the perimeter of the work, and these attitudes, finally produce results at short, medium and long terms to the organization and to the developers. The theoretician base gave support to the dissertation, which broaches the human being relation with Knowledge, Corporative Education, long-distance Education into the organization context. The inductive method was applied in this exploratory research, by means of structured questionnaire and direct observation, developed on a simple application case in the exploratory/descriptive way. The research results show the need of explicitating the ECaD politics, carried out by the company, and the following developer’s identification, planning to convert it in a continued apprenticeship. The study raises the need to recognize explicitly that the ECaD must be continued as an important facilitator of learning.